2016
DOI: 10.1108/et-06-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial skills and socio-cultural factors

Abstract: Purpose The aim of this paper is to explore how entrepreneurial skills (such as creativity, proactivity, and risk tolerance) and socio-cultural factors (such as role model and businessman image) affect secondary education students’ propensity towards entrepreneurial options in their future careers. Design/methodology/approach A sample of secondary education students in the Region of Murcia (Spain) has been used. Data were collected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 74 publications
2
27
0
3
Order By: Relevance
“…Our study's results are in line with those of Rosique-Blasco et al (2016), who showed that those individuals who have an entrepreneurial role model tend to have a better understanding of the entrepreneurial career path and also stress a greater tendency toward it. Previous studies have discussed the positive relationship between observing an entrepreneurial role model and an entrepreneurial career choice (e.g., BarNir, Watson, and Hutchins 2011;Chlosta, Patzelt, Klein, and Dormann 2012).…”
Section: Results the Insignificant Relationship Between Ese And Ei Asupporting
confidence: 90%
See 1 more Smart Citation
“…Our study's results are in line with those of Rosique-Blasco et al (2016), who showed that those individuals who have an entrepreneurial role model tend to have a better understanding of the entrepreneurial career path and also stress a greater tendency toward it. Previous studies have discussed the positive relationship between observing an entrepreneurial role model and an entrepreneurial career choice (e.g., BarNir, Watson, and Hutchins 2011;Chlosta, Patzelt, Klein, and Dormann 2012).…”
Section: Results the Insignificant Relationship Between Ese And Ei Asupporting
confidence: 90%
“…With regard to the EIs of school students', Rosique-Blasco et al (2016) conducted an empirical study with a sample of 1,244 secondary school students from Spain (average age 15 years old) to examine how skills related to entrepreneurship and entrepreneurial role models can influence the way in which secondary students choose an entrepreneurial career. The authors showed that those individuals who have an entrepreneurial role model are more prone to choose an entrepreneurial career than others.…”
Section: The Influence Of Role Models On Entrepreneurial Intentionmentioning
confidence: 99%
“…It has also been reported by GEM (2012) that the low women entrepreneurship performance in Pakistan is due to the male dominant min set. This patriarchal approach hinders the active participation of women in mainstream business activities which results in lowering their business performance (Rosique-Blasco et al, 2016). Thus, the male dominant approach is not adequately supporting women and has a negative impact on the business performance of women entrepreneurs specifically in small, medium enterprises.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…In recent times, the importance of entrepreneurial education at all levels (primary, secondary and tertiary) of educational systems has become the center of attention. The focus has been on incorporating the common entrepreneurial skills in the learners, its teaching and upgradation, influencing factors based on which students choose entrepreneurial careers (Falkang and Alberti, 2000;Gürol and Atsan, 2006;Jones et al, 2012;European Commission, 2013;Rosique-Blasco et al, 2016). The recent study of Rosique-Blasco et al (2016) contributes toward the development of entrepreneurial skills at secondary-level education, and how creativity, proactivity and the risk-taking behavior as skills makes an entrepreneurial career as a choice.…”
Section: Special Issues Of Education +mentioning
confidence: 99%